Otomatisasi Perangkap Tikus Menggunakan Sensor HC-SR04 Berbasis Arduino Uno - giant nanda eka putra; Lukman Nulhakim (LPPM STMIK ANTAR BANGSA, 2023)
Rats are animals that play a human pest and enemy, especially in the home environment. In addition to frequently eating foodstuffs that are in the house, the droppings of these rats can also bring about various diseases. Making automatic mouse trap tools is a solution to these problems, The stages used are system design, electronic design and build design. The components used are Arduino Uno R3, ultrasonic sensor HC-SR04 and micro servo This tool has a work system in the form of an ultrasonic sensor HC-SR04 as a rat detector, The floor trap will be moved by Arduino uno with the help of micro servo.